Has Private Participation in Water and Sewerage Improved Coverage? Empirical Evidence from Latin America - Clarke, George R. G.; Kosec, Katrina; Wallsten, Scott (2012)
Introducing private sector participation (PSP) into the water and sewerage sectors is difficult and controversial. Empirical studies on its effects are scant and generally inconclusive. Case studies tend to find improvements following privatisation, but they suffer from selection bias and it is difficult to generalise their results. To explore empirically the effects of private sector participation on coverage, we assemble a new dataset of connections to water and sewerage services at the city and province level based on household surveys in Argentina, Bolivia, and Brazil. The household surveys, conducted over a number of years, allow us to compile data before and after the introduction of private sector participation as well as from similar (control) regions did not privatise. Our analysis reveals that, in general, the share of households connected to piped water and sewerage improved following the introduction of private sector participation, consistent with the case study literature. We also find, however, that the share of households connected similarly improved in the control regions, suggesting that private sector participation, per se, may not have been responsible for those improvements. Results are similar when looking only at the poorest households. The share of poor households connected to piped water and sewerage increased similarly in areas both with and without private sector participation, suggesting that--in terms of connections at least--private sector participation did not harm the poor.